2017
DOI: 10.1371/journal.pntd.0005277
|View full text |Cite
|
Sign up to set email alerts
|

Eyelash Epilation in the Absence of Trichiasis: Results of a Population-Based Prevalence Survey in the Western Division of Fiji

Abstract: BackgroundThe WHO definition of trachomatous trichiasis (TT) is “at least one eyelash touching the globe, or evidence of recent epilation of in-turned eyelashes”, reflecting the fact that epilation is used as a self-management tool for TT. In Fiji’s Western Division, a high TT prevalence (8.7% in those aged ≥15 years) was reported in a 2012 survey, yet a 2013 survey found no TT and Fijian ophthalmologists rarely see TT cases. Local anecdote suggests that eyelash epilation is a common behaviour, even in the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Using a serological tool we showed that 53/66 (80%) of the cases of TF that we observed were in people who were serologically negative for prior Ct infection 10 . Clinical signs of trachoma were also a poor indicator for the need to deploy antimicrobials in Fiji, where the high prevalence of TT cases could be better explained by socio-epidemiological practices of eyelash depilation than by Ct infections 11 . The current WHO guidelines would recommend MDA in both Fiji and the Solomon Islands, but the evidence from more detailed surveys makes an argument against the likelihood that the use of antimicrobials would be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Using a serological tool we showed that 53/66 (80%) of the cases of TF that we observed were in people who were serologically negative for prior Ct infection 10 . Clinical signs of trachoma were also a poor indicator for the need to deploy antimicrobials in Fiji, where the high prevalence of TT cases could be better explained by socio-epidemiological practices of eyelash depilation than by Ct infections 11 . The current WHO guidelines would recommend MDA in both Fiji and the Solomon Islands, but the evidence from more detailed surveys makes an argument against the likelihood that the use of antimicrobials would be effective.…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently shown that a common sociocultural practice of eyelash epilation was prevalent in the Western Division of Fiji. A 2017 study [ 56 ] demonstrated that many Fijians who epilated (and who would have been classified as TT cases) in fact had no signs of scarring or entropion and were unlikely to be self-treating for the condition.…”
Section: Resultsmentioning
confidence: 99%
“…This definition implies that all epilated eyelashes were in-turned, although data suggest that field graders may have difficulty determining whether or not an epilated eyelash was in-turned before it was pulled out. 38 The meaning of “recent” within this context has never been defined, but has been interpreted by users of the system as the appearance of broken eyelashes or empty eyelash follicles.…”
Section: Discussionmentioning
confidence: 99%